POLA KOMUNIKASI ANTARBUDAYA (MUNA DAN JAWA) MAHASISWA UNIVERSITAS NEGERI YOGYAKARTA DI DAERAH ISTIMEWA YOGYAKARTA - Saharul Hariyono (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study examines intercultural communication patterns and the challenges arising from cultural differences between Munanse students (Southeast Sulawesi) and Javanese students (Yogyakarta) at Universitas Negeri Yogyakarta. The research employs a qualitative descriptive method with data collected through interviews, observations, and literature review, alongside triangulation to enhance data validity. The theoretical framework integrates sociolinguistics and intercultural communication theory initiated by William Gudykunst & Young Yun Kim. The findings reveal that communication patterns evolve through three stages: interactive, transactional, and dynamic. In the initial phase, interactions are marked by discomfort and misunderstandings due to differences in speech styles and cultural norms. Munanse students, who tend to be direct and straightforward, are often perceived as impolite by Javanese students who value politeness and indirect communication. Over time, adaptation and cultural exchange foster more open and mutual understanding. The study also identifies communication issues such as stereotypes, ethnocentrism, and pragmatic gaps. This research offers novelty by focusing on the Munanse–Javanese communication dynamic within a multiethnic campus context. The findings provide practical contributions to the development of inclusive and culturally aware higher education environments.